Influence of the Escherichia coli Nissle 1917 strain on complications of chronic experimental liver damage - Kosáková, Dita; Scheer, Peter; Lata, Jan; Doubek, J (Veterinární medicína, 2007)
The aim of the study was evaluate the influence of the probiotic Escherichia coli Nissle 1917 strain (Mutaflor® suspension) on bacterial translocation in cases of liver damage, damage to the intestinal mucosa, potential portal hypertension associated with possible development of oesophageal varices and on the bacterial population of the intestine during chronic experimental liver damage in the laboratory rat. Rats with liver damage induced by thioacetamide were divided into an experimental and control group. Experimental and control animals were applied Mutaflor and saline, respectively. Samples of blood, liver, lymph nodes and caecum for microbiological examination, of liver, duodenum and oesophagus for histological examination and of spleen for weight evaluation were collected. There were no significant differences between both groups of animals in the qualitative proportion of Staphylococcus spp., Enterococcus spp. and Proteus spp. cultured from the lymph nodes, blood and liver. The quantitative culture results on Enterococcus spp. in the caecum, liver and lymph nodes showed no significant differences between both groups. There was a significant difference between the experimental and control group in the counts of coliform bacteria. No significant differences between both groups were found in the overall damage score of the liver, duodenum and oesophagus. There were no differences in the spleen to body weight ratio of both groups. The application of Mutaflor® suspension for eight days had no recognisable effect diminishing the selected complications of chronic liver damage caused by the administration of TAA to laboratory rats.
Keywords: krysa rodu Rattus; Animals; thioacetamid; Probiotics; jaterní cirhóza; zvířata; Bacterial Translocation; Thioacetamide; Rats, Wistar; bakteriální translokace; Liver Cirrhosis; probiotika; Escherichia coli; Rats; potkani Wistar